Simulation and improvement the solar cell Cu2CdSnS4 and study the effect of absorption layer defect (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, a quadruple cell was built from the bilayer cell, which is the basis for it, where a permeable layer was added to the binary cell, which is ZnO, to become the CCTS/CdS/ZnO cell, and then another permeable layer was added, which is AZO, to become a cell with four layers similar to the practical cell. The work is focused on increasing the efficiency from 1.80% to 7.7%, meaning that we have combined the high-efficiency binary cell and the low-efficiency quadruple cell, and then we learned to improve it by taking the best thickness for all layers, and the thickness values ​​were as follows for the absorbent layer (5µm) For the buffer layer CdS is 0.2µm and the thickness of the permeation layers is ZnO and AZO is 0.2µm, the concentrations were for the absorption layer 1015cm-3, the fitting layer is 1019cm-3 and the first window  layer is 1019cm-3 and the second window  layer is 1020cm -3 and the outputs were The quadruple cell after optimization is as follows: (Voc=0.597V, Jsc=23.668mA/cm2, FF=52.48%, eta=7.43%).to make the cell closer to practical reality, defects were added to the interface, the defect type is neutral, and the values ​​of the interface defects are as follows (the energy level for the reference, which is the valence band equal to 0.6eV), (the defect density Nt equal to 1.0×1013cm-2), (the cross-sectional area for capturing the gaps and electrons 1.0×1015cm2) ,Then the defects were added to the CCTS absorbing layer of the defect type (donor, acceptor, and neutral) with fixing the interface defects at neutral and the values ​​of the absorption layer defects as follows (energy level relative to the reference valence band equals 0.6Ev), (the defect density Nt equals 1.0×1015cm- 2), (the cross-sectional area for capturing gaps and electrons is 1.0×1015cm2) and the results are close to the practical reality of the cell, which is the defect of the accepter absorbing surface (Voc=0.594V, Jsc=22.29mA/cm2, FF=52.28%, eta=6.94%) ,In this last part of the optimization process, five BSL back reflection layers were added which are (Cu2O, ZnTe, SnS, MoSo2,Cu2Te). The best back reflection layer was Cu2O, where the final cell outputs after the optimization were as follows: (Voc=0.638V, Jsc= 25.47mA/cm2,FF=47.32%,eta=7.69%).